Deformation mechanism of dislocation slip and kinking behaviour in dynamic compression response of TiZrHfNb alloy fabricated by laser directed energy deposition - Chunjie Shen; Xu Cheng; Zhuo Li; Chen Yang; Yansong Zhang; Ruiqi Li (Virtual and Physical Prototyping)
In this study, the dynamic response and deformation mechanism of TiZrHfNb RHEA fabricated by laser directed energy deposition (L-DED) were researched under a dynamic compression test at a nominal strain rate of 3500 s−1. The L-DED TiZrHfNb alloy with columnar grains exhibits exceptional mechanical properties with a uniform dynamic flow stress of 1670 ± 10 MPa and a maximum plastic strain of 0.28 ± 0.03. The dislocation slipping and kinking behaviour dominate uniform plastic deformation. First, the dislocations are primarily confined within dislocation channels due to coplanar slip, and the evolution of them in dynamic compressive deformation process has undergone spacing refinement and crossing. Furthermore, the kinking behaviour induced by the lattice rotation with the T = <011> axis denotes the work hardening effect. Particularly, the second kinking behaviour effectively relieves local stress concentration and delays fracture before the formation of adiabatic shear band (ASB).